P02 Surveillance Study of Gender Identity Disorder in Children and Adolescents. (4th June 2013) - Khadr, SN; Carmichael, P; Holt, V; Roche, E; Viner, R
Abstract : Aims: The incidence of childhood/adolescent Gender Identity Disorder (GID) is unknown. GID is an important condition where gender identity differs from biological sex. It is associated with significant distress, particularly with puberty, with much controversy internationally over the optimal timing of hormonal treatment. We examine the incidence and clinical presentation in UK and Irish children and adolescents. Methods: STUDY POPULATION: Children and adolescents aged 4–15.9 years in the UK and Republic of Ireland. DESIGN: Joint British Paediatric Surveillance Unit (BPSU) and Child and Adolescent Psychiatry Surveillance System (CAPSS) study. New cases of GID reported by clinicians over a 19-month reporting period (01-Nov-2011 to 01-June-2013) are validated against the authoritative DSM-IV-TR (2000). Exclusions include disorders of sexual differentiation and major psychosis. PRIMARY OUTCOME: Incidence of childhood/adolescent GID, calculated by dividing the number of validated cases by the base population of children/adolescents aged 4–15.9 years. Sources of denominator data: UK Office of National Statistics and the Central Statistics Office in Ireland. STATISTICAL ANALYSIS: Descriptive statistics and comparisons using two-sample t-tests/Mann-Whitney U tests for continuous data and Chi-squared/Fisher's exact tests for categorical data. Results: Preliminary descriptive data from the first nine months' surveillance (n = 80 cases, 42 males) indicate that similar numbers of males and females are affected by this condition. There is a lag of several years between median [range] onset of symptoms (6y [1–14y]) and presentation to Paediatricians or Psychiatrists (13y [4–14y]), with high levels of psychiatric co-morbidity at presentation, particularly depression (n = 15, 19%), Asperger Syndrome/autistic spectrum disorder (ASD) (n = 16, 20%) and previous self-harm (n = 24, 30%). There appears to be a relationship between pattern of presentation and co-morbidities observed at diagnosis: nearly half of BPSU cases (5/11) have a co-diagnosis of Asperger Syndrome/ASD at diagnosis compared with 16% of CAPSS cases (11/69). Depression and anxiety have only been reported among CAPSS cases. It is unclear whether these discrepancies reflect referral pathways or different diagnostic approaches. Conclusions: We present the first ever population-level data on the clinical features and presentation of childhood/adolescent GID. These data will inform clinical management, including the highly controversial debate around early pubertal suppression in this group.